Decorating Surfaces with Bidirectional Texture Functions - Zhou, Kun; Du, Peng; Wang, Lifeng; Matsushita, Yasuyuki; Shi, Jiaoying; Guo, Baining; Shum, Heung-Yeung (IEEE Transactions on Visualization and Computer Graphics, 2005)
We present a system for decorating arbitrary surfaces with bidirectional texture functions (BTF). Our system generates BTFs in two steps. First, we automatically synthesize a BTF over the target surface from a given BTF sample. Then we let the user interactively paint BTF patches onto the surface, such that the painted patches seamlessly integrate with the background patterns. Our system is based on a patch-based texture synthesis approach known as quilting. We present a raphcut algorithm for BTF synthesis on surfaces, and the algorithm works well for a wide variety of BTF samples, including those which present problems for existing algorithms. We also describe a graphcut texture painting algorithm for creating new surface imperfections (e.g., dirt, cracks, scratches) from existing imperfections found in input BTF samples. Using these algorithms we can decorate surfaces with real-world textures that have spatially-variant reflectance, fine-scale geometry details, and surfaces imperfections. A particularly attractive feature of BTF painting is that it allows us to capture imperfections of real materials and paint them onto geometry models. We demonstrate the effectiveness of our system with examples.